Targeting the innate repair receptor axis via erythropoietin or pyroglutamate helix B surface peptide attenuates hemolytic-uremic syndrome in mice - Dennhardt, Sophie; Pirschel, Wiebke; Wissuwa, Bianka; Imhof, Diana; Daniel, Christoph; Kielstein, Jan T.; Hennig-Pauka, Isabel; Amann, Kerstin; Gunzer, Florian; Coldewey, Sina M. (Frontiers in Immunology, 2022)
Hemolytic-uremic syndrome (HUS) can occur as a systemic complication of infections with Shiga toxin (Stx)-producing Escherichia coli and is characterized by microangiopathic hemolytic anemia and acute kidney injury. Hitherto, therapy has been limited to organ-supportive strategies. Erythropoietin (EPO) stimulates erythropoiesis and is approved for the treatment of certain forms of anemia, but not for HUS-associated hemolytic anemia. EPO and its non-hematopoietic analog pyroglutamate helix B surface peptide (pHBSP) have been shown to mediate tissue protection via an innate repair receptor (IRR) that is pharmacologically distinct from the erythropoiesis-mediating receptor (EPO-R). Here, we investigated the changes in endogenous EPO levels in patients with HUS and in piglets and mice subjected to preclinical HUS models. We found that endogenous EPO was elevated in plasma of humans, piglets, and mice with HUS, regardless of species and degree of anemia, suggesting that EPO signaling plays a role in HUS pathology. Therefore, we aimed to examine the therapeutic potential of EPO and pHBSP in mice with Stx-induced HUS. Administration of EPO or pHBSP improved 7-day survival and attenuated renal oxidative stress but did not significantly reduce renal dysfunction and injury in the employed model. pHBSP, but not EPO, attenuated renal nitrosative stress and reduced tubular dedifferentiation. In conclusion, targeting the EPO-R/IRR axis reduced mortality and renal oxidative stress in murine HUS without occurrence of thromboembolic complications or other adverse side effects. We therefore suggest that repurposing EPO for the treatment of patients with hemolytic anemia in HUS should be systematically investigated in future clinical trials.